Examining demographic moderation in B2B logistics: Insights from boxplot visualization and MGA of brand relationship drivers - Nguyen , Thi Thuy Giang; Tran , Thi Tra Giang; Bui , Thi To Loan; Nguyen , Tran Tu Anh; Nguyen , Thi Huyen (Journal of Finance - Marketing Research, 2025)
This study investigates the impact of demographic factors on brand loyalty in the B2B logistics sector, addressing a key gap in existing research by integrating both visual and statistical tools. Specifically, it examines how demographic characteristics, such as business age, size, logistics expenditure, annual revenue, and the number of trusted logistics providers, moderate the relationships between brand image, brand love, brand engagement, and brand loyalty. To achieve this, the study employs a dual-method approach: Boxplots in RStudio are used to visualize differences in brand loyalty across demographic groups, while Multi-Group Analysis (MGA) within PLS-SEM statistically tests moderation effects. Data were collected from 145 logistics clients in Ho Chi Minh City. Findings reveal that mid-sized businesses and those allocating 21–30% of their budgets to logistics report the highest brand loyalty. Smaller firms prioritize reliability, while larger firms favor technology-driven services. Notably, clients with 2–5 trusted logistics providers demonstrate stronger loyalty, highlighting the importance of reliability and flexibility for logistics service providers (LSPs) aiming to become preferred partners. This research provides actionable insights for LSPs to tailor brand strategies to specific client segments, enhancing loyalty and sustaining long-term B2B relationships.